ALJABAR C* DARI RUANG MATRIKS M_n (B(H)) - Khaerudin Saleh; Rustam Rustam; Yulinda Eliskar (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2023)
Let be a Hilbert space. The set of bounded operators on the Hilbert space denotes by can be identified as an C*-Algebra. Let be a Matrix vector space over the field . By using *isomorphism it will be proven that is also a C*-algebra.